25th ANNIVERSARY OF CLONING BY SOMATIC-CELL NUCLEAR TRANSFER: Scientific and technological approaches to improve SCNT efficiency in farm animals and pets. Issue 1 (11th June 2021) - Loi, Pasqualino; Palazzese, Luca; Scapolo, Pier Augusto; Fulka, Josef; Fulka, Helena; Czernik, Marta
Abstract : The birth of Dolly through somatic cell nuclear transfer (SCNT) was a major scientific breakthrough of the last century. Yet, while significant progress has been achieved across the technics required to reconstruct and in vitro culture nuclear transfer embryos, SCNT outcomes in terms of offspring production rates are still limited. Here, we provide a snapshot of the practical application of SCNT in farm animals and pets. Moreover, we suggest a path to improve SCNT through alternative strategies inspired by the physiological reprogramming in male and female gametes in preparation for the totipotency required after fertilization. Almost all papers on SCNT focused on nuclear reprogramming in the somatic cells after nuclear transfer. We believe that this is misleading, and even if it works sometimes, it does so in an uncontrolled way. Physiologically, the oocyte cytoplasm deploys nuclear reprogramming machinery specifically designed to address the male chromosome, the maternal alleles are prepared for totipotency earlier, during oocyte nuclear maturation. Significant advances have been made in remodeling somatic nuclei in vitro through the expression of protamines, thanks to a plethora of data available on spermatozoa epigenetic modifications. Missing are the data on large-scale nuclear reprogramming of the oocyte chromosomes. The main message our article conveys is that the next generation nuclear reprogramming strategies should be guided by insights from in-depth studies on epigenetic modifications in the gametes in preparation for fertilization.